2011
DOI: 10.1097/id.0b013e318211fe1b
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dislodging Forces on Mandibular Implant Attachment-Retained Overdenture

Abstract: : This study has demonstrated that implant overdenture attachment design and dislodging forces may significantly influence stress/strain magnitude around implants; the higher the retention (resistance to dislodging forces) of the attachments the more the transferred stresses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 12 publications
1
23
0
Order By: Relevance
“…The increased VBL around posterior implants compared to anterior implants in GII is in agreement with findings of in vitro studies (Elkerdawy & Radi ; ELsyad et al. ) and may be due to most of the masticatory forces are concentrated in the posterior area.…”
Section: Discussionsupporting
confidence: 90%
“…The increased VBL around posterior implants compared to anterior implants in GII is in agreement with findings of in vitro studies (Elkerdawy & Radi ; ELsyad et al. ) and may be due to most of the masticatory forces are concentrated in the posterior area.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, the wide use of in vitro studies including the FE method is due to the fact that in vivo studies cannot be repeated under the same conditions, because of the wide variance of histological structures from one patient to the other. 33 The results of this study may provide a broader understanding about potential stress concentration locations. Long-term clinical research is required to determine the influence of observed stress levels on tissue and prosthesis function.…”
Section: Discussionmentioning
confidence: 83%
“…Unlike other in vitro evaluation techniques, the FE method can quantify the physiological strain thresholds of human jawbones. Furthermore, the wide use of in vitro studies including the FE method is due to the fact that in vivo studies cannot be repeated under the same conditions, because of the wide variance of histological structures from one patient to the other 33 . The results of this study may provide a broader understanding about potential stress concentration locations.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies reported that the retentive forces of magnetic attachments were less than other attachments 14,15 . However, this reduced retention was found to generate the least stresses in peri-implant bone during overdenture dislodgement 16 . They also exhibited fewer strains under occlusal loading when compared to ball and bar attachments 15,17 .…”
Section: Magnet Versus Ols Attachments For Implant Overdentures: a Stmentioning
confidence: 95%